2021
DOI: 10.1155/2021/7260507
|View full text |Cite
|
Sign up to set email alerts
|

Medical Students’ Perception of the Educational Environment at College of Medicine: A Prospective Study with a Review of Literature

Abstract: Dundee Ready Education Environment Measure (DREEM) inventory has been exhaustively used to evaluate the education environment (EE), especially in the health sector to identify the strengths and weaknesses of the program. This study was designed to investigate the medical students’ perceptions about the education environment (EE) of the College of Medicine (COM), Jeddah. This cross-sectional study was carried out on medical students and conducted between May and August 2020. A predesigned DREEM questionnaire wr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 56 publications
2
5
0
Order By: Relevance
“…Our students believed PBL lead to in-depth analysis and enhanced critical thinking with a balance division of work. This was also in line with our previous published studies on the educational environment using DREEM tool [28] and the student's feedback on choosing effective course coordinator [29]. In this study there's a clear improvement in satisfaction for all the three domains by the male students while the female's satisfaction improved only for the problems.…”
Section: Discussionsupporting
confidence: 91%
“…Our students believed PBL lead to in-depth analysis and enhanced critical thinking with a balance division of work. This was also in line with our previous published studies on the educational environment using DREEM tool [28] and the student's feedback on choosing effective course coordinator [29]. In this study there's a clear improvement in satisfaction for all the three domains by the male students while the female's satisfaction improved only for the problems.…”
Section: Discussionsupporting
confidence: 91%
“…Among different educational levels or study phases (preclinical and clinical), significant differences were found among students from medical colleges [39,42,46,49,52,55,57], applied medical science colleges [63,65], and dental colleges [20,74]. Similar conclusions were achieved worldwide [17,24,31,39,75].…”
Section: Significant Differences In Gender and Educational Levelssupporting
confidence: 53%
“…Few articles mentioned significant differences among colleges [46,54,64], universities [47,60], and specialties [62,64], and other studies indicated significant differences among parameters such as marital status and cumulative grades [69,73]. Among different educational levels or study phases (preclinical and clinical), significant differences were found among students from medical colleges [39,42,46,49,52,55,57], applied medical science colleges [63,65], and dental colleges [20,74]. Similar conclusions were achieved worldwide [17,24,31,39,75].…”
Section: Significant Differences In Gender and Educational Levelsmentioning
confidence: 99%
“…Emphasis needs to place on making the learning atmosphere stress-free by encouraging students to interact and participate more both in physical and virtual platforms. A healthy and efficient educational environment is essential for nurturing both the professional and personal growth of future health professional students ( Aga et al, 2021 ). The COVID-19 pandemic has significantly impacted medical schools around the world, with the Middle East being no exception ( Gordon et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%